An Eye for Detail: the Dallard years - McCarthy, Christine (Architectural History Aotearoa, 2021)
It is often considered that the 1930s was a mundane period in the history of New Zealand prison architecture. This paper re-evaluates this conclusion by examining the specific aspect of prison interior architecture and the incremental changes that occurred to prison buildings during this period of New Zealand’s prison history.